KARAKTERISTIK PENDIDIKAN ISLAM - Dudung Suryana; Fuad Hilmi; Ina Maryana (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
Islamic education is education for all human beings. Where he brings goodness and suitability for all of humanity. Not limited to one item of each period. On a particular group of people, or nation of nations. However, it is a global human education for all human. Indeed characteristics of Islamic education stressed that he was the only special education, education that he has a special character that is not possible compared to other education-education that appear to have similarities in some of the characters, just different in each emphasis contents. Specificity and this privilege is clear as mentioned. The meaning of education is characteristic traits, traits that distinguish with any other education. These characteristics are sometimes partly the same as between one another in some educational establishments. However, the characteristics that should be portrayed with a true depiction again be giving the view that education and teaching.